Kemampuan Membaca Kritis dan Penguasaan Kalimat Efektif : Faktor yang Mempengaruhi Kemampuan Menulis Karya Ilmiah - Fitri, Rahayu; Sartika, Rina (Universitas Terbuka, 2024)
The aims of this research is to describe the contribution between critical reading skills and mastery of effective sentences on the ability to write scientific papers of phase F students at SMK Negeri 6 Padang. This research is quantitative research using correlational methods. In this research, the population consisted of ten classes of class XI students at SMK Negeri 6 Padang in the 2022/2023 academic year with a total of 334 students. The sampling technique used was a simple random technique. The instruments in this research are objective tests with multiple choice types and performance tests. Before the data was analyzed, analysis requirements were tested, namely the normality test with the Liliefors test, homogeneity test with the Cohran test, and the linearity test. In this study, the data were analyzed using simple and multiple correlation tests. It can be concluded that there is a significant relationship between critical reading ability and mastery of effective sentences together on the ability to write scientific papers. Based on the results of testing variables X1 and X2 together against Y, the rxy result was 0,42 with a calculated fvalue = 6,69 and ftable = 3,34. The contribution made by the ability to read critically and mastery of effective sentences together to the ability to write scientific papers is 17,64%.